Innovation in Diversification of Various Processed Shells of Northern Coastal Women Craftsmen with High Economical Value in Surabaya Indonesia - Widiana, Muslichah Erma; Rinurwati; Farida Agustini Widjayati; Meidita Sinantryana Widyaswari (Archives of Business Research, 2020)
A research-based community service program titled Diversified Innovation of Processed Shellfish from Northern Coastal Craftsmen with Economic Value and High Nutrition Potential in the Kulon-Kedung Cowek Cumpat Area Surabaya (1) Mitra1 Ibu Siti Chotimah located at Jl Cumpat Kulon Baru I / 88-Kedung Cowek Surabaya (1) 2) Mitra2 The women of fishermen’s wives in the Cumpat Kulon area. Problem: During this time the production and marketing process is very inefficient and ineffective for SMEs that want to improve into a home industry, even though the capacity and high productivity are as follows: 1) to produce various processed shells of Cumpat Kulon-Kedung Cowek Surabaya women who use materials traditional natural spices that are healthy mixing ingredients and spices so far have used manual labor so that the mixing of herbs can not be maximized. 2) To smooth the shells as a superior and basic material is still with a traditional improvised tool in the form of mortar. 3) Marketing is not widely known yet it is superior to the north coast. The solution: 1) the use of a motor-powered mixer machine Specifications:Voltage: 220v Frequency: 50 / 60hz Power: 450 watt Engine Weight: 57 kg Machine diameter: 45 x 36.6 x 60.6 cm 2) use of meat grinder Front hole diameter 9 cm. Upper hole diameter 12 cm. Grinding height 24 cm. meat grinder Front hole diameter 9 cm. Upper hole diameter 12 cm. Grinding height 24 cm. 3) Providing training in creativity and innovation in the manufacture of products from shellfish and e-marketing of coastal products from Kenjeran to partners1 and partners2. Methods: (1) Design, build, maintain, use of a motor-powered mixer machine Specifications: Voltage: 220 frequency: 50/60 Hz Power: 450 watts Machine Weight: 57 kg. Machine diameter: 45 x 36.6 x 60.6 cm (2) Design, build, care for using meat grinder Front hole diameter 9 cm. Upper hole diameter 12 cm. Grinding height 24 cm. (3) Training, practice and mentoring transmit the mindset and behavior of an entrepreneur to students until he behaves and is entrepreneurial for partners1 and partners as well as e-marketing with smartphones.